Phytochemical screening and antibacterial activity of selected mistletoes of Kathmandu Valley (Botanica Orientalis: Journal of Plant Science, 2020)
Mistletoes are a unique group of green, parasitic plants which require host plants for their survival. Among the 19 species of mistletoes so far reported from Nepal, the majority of them have traditionally been used as fodder and to cure various ailments, including nausea, vomiting, and bloody diarrhoea. In this study, seven common mistletoe species were collected from the Kathmandu Valley and surrounding region in Central Nepal. Methanolic extracts of the plant samples were selected for qualitative phytochemical screening, and antibacterial activity against four ATCC (American Type Culture Collection) bacterial strains (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and S. epidermidis). Sonication method was used for the extraction and resulted with the highest percentage yield of extract for Viscum album (24.26 %) and lowest for Scurrula parasitica (11.86 %). Qualitative phytochemical screening showed the presence of saponin, flavonoid, steroid, terpenoid, glycosides, alkaloids and phenol. Among the methanolic extracts of seven species of mistletoe, only four have shown antibacterial properties against the bacterial strains used. Methanolic extracts of Helixanthera ligustrina and Viscum articulatum showed antibacterial activity against all tested organisms. Macrosolen cochinchinensis showed the significant inhibition in all bacteria except S. aureus. Similarly, the extract of Scurrula parasitica was found ineffective against gram-negative bacteria (E. coli and P. aeruginosa) but found effective against gram-positive bacteria (S. aureus and S. epidermidis).